PENGGUNAAN APLIKASI RENDERFOREST SEBAGAI MULTIMEDIA PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE STAD - Amsidi, Mukmin (Jurnal Edukasi, 2025)
Education is currently in the midst of the covid-19 pandemic, so that one of the alternatives used by the current government in the learning process is online and offline learning or what we usually know as blended learning, due to the demands of the learning process that must be interesting, new innovations are needed remembering Mathematics Learning is something that is considered difficult by many people. This study aims to (1) develop interesting learning media using applications (2) Attract students' interest in learning mathematics with learning videos. The research approach used in this research is R&D using the Nano Learning learning method and the ADDIE product development model. The subject in making this learning video is Class VII MTs 01 Alor. Data collection techniques used are questionnaires and documentation.